Pengaruh Perbedaan Lama Waktu Distress Kronis Terhadap Perubahan Jumlah Osteoblas padaTulang Alveolar Tikus Sprague Dawley (The Effect of Differentiation Chronic Distress Duration of Osteoblast Cells Number in Alveolar Bone of Sprag - Hayyu Rizky Nur Rahma; Suhartini . (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Background: Stress is a phenomenon that can occur to all organisms. Pathological stress is called distress. Distress in the long term is called chronic distress. Chronic distress will increase the secretion of cortisol, which is inducting osteoblast apoptotic and reduce osteoblast number. Purpose: Analizing the effect of differentiation chronic distress duration of osteoblast cells number in aveolar bone of Sprague dawley rats changing. Methods: Using Sprague Dawley rats with total sample of 24 animals. The rats were given an electric shock stressor (Electrical Foot Shock) as distress chronic for 7, 14, and 28 days. Stressors were given for 30 minutes at 9 a.m every day during the treatment period. The amount of electrical current is 2-8 mA, 48 V voltages and 0.5 Hz frequency. Osteoblast number were observed histologically using a microscope with 400x magnification. Results: The results showed a significant difference of 0.00 (p <0.05) between variables. Significant differences were found in the SPF 0 with SPF 4. Conclusion: Differences long time proven chronic distress affects the decrease in the number of osteoblasts in alveolar bone Sprague Dawley rats. Keywords: Alveolar bone, chronic distress, osteoblast, Sprague daw